4. Object and Objecthood in Post-Minimal Sculpture - Vereștiuc Mihai (Sciendo, 2022)
In this material, we analyse the way in which a paradigmatic period for the evolution of art and sculpture as we see it today, the years 1960-1970, shaped the contemporary perception of the visual arts, in terms of reconnecting a spiritual approach and the art manifestation and perceptibility. The theme allows a radiographic introspection into the visual expressions, the diversity of materials, techniques, artistic and aesthetic solutions. The main goal is to facilitate the understanding of the mechanisms that led to nowadays perceptions of art (and of sculpture, as the main vehicle of operating with objectual and space). As most of the minimalist and post-minimalist sculpture orientations can be analysed though the perspective of various prominent artists or researchers such as Donald Judd and Hal Foster, we also assist to major shifts in institutionalizing anti-aesthetic or less-traditional art movements.